Bioactive constituents, nutritional benefits and woody food applications of Castanea mollissima: A comprehensive review. (1st November 2022) - Zhang, Su; Wang, Litao; Fu, Yujie; Jiang, Jian-Chun
Highlights: Castanea mollissima is an outstanding species that represents a valuable natural resource for the global populations. Castanea mollissima shells were highlighted as remarkable sources of functional ingredients with promising applications in food and nutraceutical fields. The botanical characteristics, nutritional compositions, biological activities and processing technology of the whole chestnut were critically evaluated. Investigations on quality evaluation and sustainable utilization of Castanea mollissima are expected. Abstract: Castanea mollissima BL. is an outstanding species that represents a valuable woody food resource due to consumers' salient beliefs in the health benefits of chestnut consumption. Besides chestnut kernel, the discarded shells of chestnut were highlighted as remarkable sources of functional ingredients with promising applications in food, nutraceutical, pharmaceutical and industrial raw materials, mainly as natural antioxidants and effective prebiotics. Phytochemical studies reported not only antioxidant and antimicrobial activities, but also anti-inflammatory, anticancer, hypolipidemic, hypoglycemic and neuroprotective activities. This review aims to summarize the botanical characteristics, nutritional compositions, biological activities and comprehensive utilization of the whole C. mollissima, emphasizing the value of sustainable use in the recovery of bioactive compounds and their potential applications in food and other industries. It will provide a reference for the further development of C. mollissima in the field of multi-functional food and will inspiring investigations on the comprehensive utilization of chestnut and their by-products.